The Toxicological Effects of Mercury Exposure in Marine Fish - Zheng, Na; Wang, Sujing; Dong, Wu; Hua, Xiuyi; Li, Yunyang; Song, Xue; Chu, Qingwen; Hou, Shengnan; Li, Yang (Bulletin of environmental contamination and toxicology, 2019)
Since the Minamata incident in Japan, the public have become increasingly aware of the negative health effects caused by mercury pollution in the ocean. Consequently, there has been significant interest in the health of humans eating fish exposed to mercury (Hg). However, the toxicity of mercury to the marine fish themselves has received far less attention. In this review, we summarize mercury accumulation in marine fish and the toxicological effects of mercury exposure. Results showed that the bioaccumulation of mercury in marine fish was highly variable, and its concentration was affected by the specific physiological and ecological characteristics of different fish species. Mercury exposure can produce teratogenic, neurotoxic effects, and reproductive toxicity. These effects can then cause harm to cells, tissues, proteins and genes, and ultimately, the survival, growth, and behavior of marine fish. Future studies should afford more attention to the toxicological effect of mercury exposure upon marine fish.